2022
DOI: 10.1155/2022/1704172
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Modification Profile in Bovine Mammary Epithelial Cells Treated with Heat-Inactivated Staphylococcus aureus

Abstract: The symptoms of mastitis caused by Staphylococcus aureus (S. aureus) in dairy cows are not obvious and difficult to identify, resulting in major economic losses. N6-Methyladenosine (m6A) modification has been reported to be closely associated with the occurrence of many diseases. However, only a few reports have described the role of m6A modification in S. aureus-induced mastitis. In this study, after 24 h of treatment with inactivated S. aureus, MAC-T cells (an immortalized bovine mammary epithelial cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Bacterial infection can affect the epigenetics modification in host cells, and m6A methylated genes have been reported to be changed in SA‐induced epithelial cell line (Li et al, 2022). Therefore, we analyzed m6A modification level and the associated regulatory genes in SA‐induced BMSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial infection can affect the epigenetics modification in host cells, and m6A methylated genes have been reported to be changed in SA‐induced epithelial cell line (Li et al, 2022). Therefore, we analyzed m6A modification level and the associated regulatory genes in SA‐induced BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…N6 methyl adenosine (m6A) modification is a kind of epigenetic modification widely existing in eukaryotic cells, and it can affect the expression level of messenger RNA (mRNA) by regulating the process of precursor splicing, translation, and stability of mRNA (Feng et al, 2018). Previous evidence has suggested that the mRNA levels of m6A regulatory genes, including methyltransferase 3 (METTL3), methyltransferase 14 (METTL14), WT1 associated protein (WTAP), and alkB homolog 5 (ALKBH5), show an upregulating trend in SA‐induced bovine mammary epithelial cell, leading to significant changes in multiple RNA expression levels within cells (Li et al, 2022). Another research also demonstrates that m6A modification on 63 circular RNAs are changed in SA‐infected bovine mammary epithelial cells compared with the control cells, and the differentially modified molecules are closely related to cellular injury (Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Replicating telomere shortening is generally prolonged by telomerase, which most somatic cells lack [ 27 , 28 ]. The other cause maybe the chronic oxidative stress caused by HKSA [ 29 , 30 ], oxidative stress causes telomere damage by directly attacking the guanine triad of telomeres, or by attacking telomere protective complexes shelterin, which contains TRF1, TRF2, RAP1, POT1, TIN2, and TPP1, resulting in loss of telomere protection [ 9 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventh, the sorting mechanism of mastitis-related exosome cargo and the molecular mechanism mediating intercellular communication remain unclear; these areas of inquiry in mastitis research are still in their infancy. Three atlas-based articles describe the m6A modification of mRNA and circular RNA (circRNA) in MAC-T cells after E. coli or S. aureus infection [ 156 , 157 , 158 ]. Considering the function of m6A modification in promoting miRNA maturation [ 159 ], study into the role played by m6A in mastitis exosomal cargo sorting is warranted.…”
Section: Challenges Of Using Exosomes In the Diagnosis And Treatment ...mentioning
confidence: 99%